The Effect of Deforestation Intensity and Land Cover Change on Forest Carbon Emissions in Tropical Forest Areas of East Kalimantan, Indonesia - Christian Soleman Imburi; Novaldi Laudi Angrianto (Westscience Press, 2026)
This study aims to examine the effect of deforestation intensity and land cover change on forest carbon emissions in the tropical forest region of East Kalimantan, Indonesia. A quantitative approach was employed using primary data collected from 65 respondents through a perception-based survey measured with a Likert scale. Data analysis was conducted using SPSS version 25, including descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that deforestation intensity has a positive and significant effect on forest carbon emissions, while land cover change also has a positive and more dominant effect. Simultaneously, both variables significantly influence carbon emissions, with a coefficient of determination (R²) of 0.508, indicating that 50.8% of the variation in carbon emissions can be explained by the model. These findings suggest that increased deforestation and land cover transformation contribute significantly to higher carbon emissions. The study highlights the importance of integrated forest management and sustainable land-use planning to mitigate environmental degradation and support climate change mitigation efforts.